Déjà vu latinoamericano (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2019)
Every time Latin America comes to the attention of Italian public opinion due to political turbulence and street protests, Italy is generally taken by surprise. Suddenly the Latin American region is represented as an exotic land, victim of an unmotivated collective hysteria that overwhelms everything with its devastating fury, institutions, societies, economies. Stereotypes of a distant time resurface, some of them originating in the nineteenth century, when European and American travellers and merchants contributed to the construction of an image of backwardness and incivility of the subcontinent. The truth is that dissent, discontent, rebellion and numerous other phenomena recur “periodically” in Latin America, because they have to do with structural problems that have never been solved, problems inscrutable to superficial analyses that do not take into proper consideration the history of this region
Keywords: Latin America; Italian Public Opinion; Latin America; structural problems; Italiana public opinion; sterotypes; historical analysis